The unorthodox evolution of major merger remnants into star-forming spiral galaxies - Sparre, Martin; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2017)
Galaxy mergers are believed to play a key role in transforming star-forming disc galaxies into quenched ellipticals. Most of our theoretical knowledge about such morphological transformations does, however, rely on idealized simulations where processes such as cooling of hot halo gas into the disc and gas accretion in the post-merger phase are not treated in a self-consistent cosmological fashion. In this paper, we study the morphological evolution of the stellar components of four major mergers occurring at z = 0.5 in cosmological hydrodynamical zoom simulations. In all simulations, the merger reduces the disc mass fraction, but all galaxies simulated at our highest resolution regrow a significant disc by z = 0 (with a disc fraction larger than 24 per cent). For runs with our default physics model, which includes galactic winds from star formation and black hole feedback, none of the merger remnants are quenched, but in a set of simulations with stronger black hole feedback, we find that major mergers can indeed quench galaxies. We conclude that major merger remnants commonly evolve into star-forming disc galaxies, unless sufficiently strong active galactic nucleus feedback assists in the quenching of the remnant.